Extended Depth-of-Focus Intraocular Lens Implantation in Patients with Age-Related Macular Degeneration: A Pilot Study - Thananjeyan AL; Siu A; Jennings A; Bala C (Clinical Ophthalmology, 2024)
Akshaya Lakshmi Thananjeyan,1 Anna Siu,2 Angela Jennings,2 Chandra Bala2 1Emergency Department, St. Vincent’s Hospital, Sydney, NSW, Australia; 2Personal-Eyes, Sydney, NSW, AustraliaCorrespondence: Chandra Bala, Personal-Eyes, 2/33 York St, Sydney, NSW, 2000, Australia, Tel +61-88337111, Email chandrabala.eye@gmail.comPurpose: To assess visual outcomes of the implantation of a non-diffractive extended depth of focus (EDOF) intraocular lens (IOL) in patients with age-related macular degeneration (AMD).Setting: Ophthalmology practice, Sydney, Australia.Design: Retrospective chart review.Methods: Patients with AMD undergoing cataract surgery and receiving non-diffractive EDOF AcrySof IQ Vivity IOL implantation over a 2-year period were identified. Corrected distance visual acuity (CDVA), distance-corrected near visual acuity (DCNVA; 50 cm), contrast sensitivity, central foveal thickness, VF-14 questionnaire results, and quality of life where available were analyzed.Results: A total of 28 sequential patients (51 eyes) were included in this pilot study (46% male, mean age 77.4 years). Of 27 eyes that had late AMD, 17 (63%) had wet AMD. Mean patient preoperative CDVA was logMAR 0.32± 0.29. Postoperative monocular CDVA and DCNVA were logMAR 0.20± 0.25 and N9± 5 (range N5–N36), respectively. Eyes achieving postoperative CDVA of Snellen 6/5– 6/12 (n=42, 82%), 6/15– 6/24 (n=7, 14%), and greater than 6/24 (n=2, 4%) achieved a mean DCNVA of N8 (range N5–N10), N13 (range N10–N18), and N27 (range N18–N36), respectively. Eyes achieving CDVA of Snellen 6/5– 6/12 showed contrast sensitivity within the normal range. On postoperative VF-14 questionnaire, patients with CDVA of Snellen 6/5– 6/12 reported minimal visual impairment, while patients with CDVA greater than 6/15 reported mild impairment. A majority of patients (96%, n=27) were satisfied with the improvement in quality of life postoperatively. No intraoperative complications were reported.Conclusion: The EDOF AcrySof IQ Vivity IOL provides improved near vision proportional to distance vision in patients with early AMD.Keywords: age-related macular degeneration, cataract, intraocular lens, extended depth of focus, non-diffractive